Rights to manage the forest cooperatively and equitably in forest-rich and forest-poor contexts - Tchingkawa B.; Brocklesby, M.A.; Tiani, A.M.; Sardjono, M.A.; Porro, R.; Salim, A.; Colfer, C.J.P. (Resources for the Future and Center for International Forestry Research, 2001)
This chapter examines the hypothesis that sustainable forest management (as represented by currently good quality forest) is correlated with acknowledgement of the rights of concerned stakeholders to manage the forest. It used a pebble sorting method, designed to assess the allocation of rights to manage forests among stakeholders, in sites in Indonesia, Cameroon and Brazil. It concludes, guardedly, that greater management rights for local communities are related to sustainable forest management; though it reiterates authors concern that good forest quality in the present cannot in fact serve as a proxy for good forest management.